Prinsip Sabat Bagi Restorasi Kehidupan Masyarakat Perkotaan - Ferdi Toding Bunga (TRANSFORMATIO: Jurnal Teologi, Pendidikan, dan Misi Integral, 2024)
The Sabbath principle has an important role in the restoration of complex urban communities. Cities as centers of economic and social activity are often faced with various challenges such as social inequality,  poverty, labor exploitation, flexing , and environmental degradation. By adhering to the Sabbath principle, it is hoped that urban communities can adopt a healthy lifestyle and ensure that economic benefits are felt by all levels of society. The research method of this paper uses library research methods. This method involves analysis, synthesis, and interpretation of previously published information in the form of books, dissertations, journal articles, reports, online sources, and other written works relevant to the topic of the Sabbath. The Sabbath, as a holy day, has not only spiritual influence but also significant social impact. First, the principle of Sabbath as the basis for liberation from modern slavery. This section emphasizes the importance of remembering origins and liberation, and promoting the values of equality, justice and social solidarity. This principle emphasizes that balance in life, both spiritually and socially, is the key to creating a just and prosperous society and reflects God's role as liberator. Second, the principle of Sabbath as the basis for a self-sufficient lifestyle is still very relevant in facing the challenges of urban society today. In the midst of city life that offers excessive consumption and economic imbalance, a self-sufficient lifestyle helps us to avoid greed, prioritize economic justice, and share with those who are poor and needy. Third, the Sabbath principle is a regulation of the rhythm of life that God has given us, so that we can properly understand the need for rest for our body and soul. Fourth, the Sabbath also has an important role in restoring various things in the lives and economy of urban communities. The Sabbath principle has an important role in restoring social relations, maintaining economic stability, improving performance, and supporting environmental conservation. By understanding and practicing the concept of Sabbath, urban communities can build a balanced society with the values of equality, justice and solidarity.